WOMEN’S LINGUISTIC FEATURES IN DISNEY ANIMATED MOVIE: BRAVE (2012) - INDI NURALIFA SUBYANTARI, 121411231022 (2018)
Studies about the relation between language and gender has been conducted from various viewpoints. One of them, women’s language can be examined in various domains such as a movie. This study intends to identify women’s linguistic features and its function from Merida’s utterances, which is the main female character in Brave (2012). Merida is depicted as a strong princess who likes to do men activity, and it is different from the princess in general. Theory from Lakoff (1975) and Jakobson (1960) are applied to analyze the data. This study had been conducted through a qualitative method. The result of this study shows that there are nine linguistic features used by Merida based on Lakoff’s (1975) theory. Those features cover lexical hedges, tag question, rising intonation, ‘empty’ adjectives, intensifiers, ‘superpolite’ form, hypercorrect grammar, avoidance of strong words, and emphatic stress. Furthermore, the writer also found that those women’s linguistic features carries five of six functions based on Jakobson (1960) which are referential function, emotive function,conative function, phatic function, and metalingual function. Therefore, the women’s linguistic features that performed by Merida shows that Merida’s activities which are related to men does not influence her language.